Relationship between dietary protein, serum albumin, and mortality in asthmatic populations: a cohort study - Zhuang, Rongjuan; Liao, Jiaxin; Giri, Mohan; Wen, Jun; Guo, Shuliang (Frontiers in Immunology, 2024)
Background: Currently, there is limited research on the correlation between protein levels in the body and asthma. We used data from the NHANES to explore the relationship of dietary protein, serum albumin, with mortality in individuals with asthma to better understand their impact on asthma.Method: This investigation involved 3005 individuals with asthma from the NHANES dataset.Studying potential links between dietary protein, serum albumin, and mortality in asthmatic populations utilized the Cox proportional hazards models, trend test, restricted cubic splines (RCS), and Kaplan-Meier survival analysis. Furthermore, subgroup analyses were carried out to explore these connections within specific populations.Result: After considering all potential variables, multivariate Cox proportional hazard models proved that dietary protein intake did not have an independent connection with all-cause mortality, but serum albumin was inversely linked with all-cause mortality. Each unit rise in serum albumin (g/l) was linked to a 13% decrease in the likelihood of all-cause mortality. RCS confirmed a negative and linear connection of serum albumin with all-cause mortality. The Kaplan-Meier survival curve suggested that asthmatic adults with greater serum albumin levels had a decreased risk of mortality compared to those with lower levels.The investigation proved a negative linear connection of serum albumin with all-cause mortality in asthma patients. However, there was no independent link discovered of dietary protein intake with mortality. This indicates that serum albumin could be a significant factor in predicting long-term outcomes for asthma patients.